2016
DOI: 10.1371/journal.pone.0151999
|View full text |Cite
|
Sign up to set email alerts
|

An IRF5 Decoy Peptide Reduces Myocardial Inflammation and Fibrosis and Improves Endothelial Cell Function in Tight-Skin Mice

Abstract: Interferon regulatory factor 5 (IRF5) has been called a “master switch” for its ability to determine whether cells mount proinflammatory or anti-inflammatory responses. Accordingly, IRF5 should be an attractive target for therapeutic drug development. Here we report on the development of a novel decoy peptide inhibitor of IRF5 that decreases myocardial inflammation and improves vascular endothelial cell (EC) function in tight-skin (Tsk/+) mice. Biolayer interferometry studies showed the Kd of IRF5D for recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Altogether, these data show that IRF5 represents a particularly valuable, dual-function therapeutic target to treat autoimmune and inflammatory diseases. To date, this is the first report to our knowledge of a selective IRF5 inhibitor that directly binds to IRF5 to inhibit nuclear translocation and has in vivo clinical efficacy in murine models of lupus (39,83,84).…”
Section: Discussionmentioning
confidence: 94%
“…Altogether, these data show that IRF5 represents a particularly valuable, dual-function therapeutic target to treat autoimmune and inflammatory diseases. To date, this is the first report to our knowledge of a selective IRF5 inhibitor that directly binds to IRF5 to inhibit nuclear translocation and has in vivo clinical efficacy in murine models of lupus (39,83,84).…”
Section: Discussionmentioning
confidence: 94%
“…More recently, alterations of IRF5 levels were also linked to obesity and its comorbidities such as nonalcoholic liver disease (NASH) and type 2 diabetes . Interestingly, protective effects seen in IRF5 ko mice are due to the defect of its repressive activity, emphasizing therapeutic opportunities via manipulating IRF activity, in line with recent attempts to develop decoy peptide inhibitors .…”
Section: Context Matters: How Irf5 Activation Versus Repression Pathwmentioning
confidence: 92%
“…The homodimeric figure is presented for easier viewing of the region where the phosphorylated tail domain of IRF5 binds to form a homodimer. This figure has been previously published 21 .…”
Section: Figurementioning
confidence: 95%
“…Analysis software showed that IRF5 binds to IRF5D with a K d of 3.72 ± 0.75 × 10 −6 M (mean ± SD, n = 3). This figure has been previously published 21 .…”
Section: Figurementioning
confidence: 95%
See 1 more Smart Citation